2015
DOI: 10.1039/c4ra15222k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the optical and dielectric properties of calcium copper titanate CaxCu3−xTi4O12 nanopowders

Abstract: The present study acts as a simple and effective way in the synthesis and characterization of CCTO with tunable optical and dielectrical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Turky et al [40] demonstrated that without any dopant, only by controlling the chemistry and engineering, the interfacial regions at the grain boundaries, the dielectric loss can be suppressed remarkably while retaining the giant dielectric constant. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Finally, chung et al [41] prepared pellets sintered in a tubetype furnace at 1100°C in air for 3 to 20 h and removed immediately to room temperature without any furnace-cooling.…”
Section: Synthesis Methods Precursors ɛ' Tan δ Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Turky et al [40] demonstrated that without any dopant, only by controlling the chemistry and engineering, the interfacial regions at the grain boundaries, the dielectric loss can be suppressed remarkably while retaining the giant dielectric constant. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Finally, chung et al [41] prepared pellets sintered in a tubetype furnace at 1100°C in air for 3 to 20 h and removed immediately to room temperature without any furnace-cooling.…”
Section: Synthesis Methods Precursors ɛ' Tan δ Referencesmentioning
confidence: 99%
“…Turky et al . demonstrated that without any dopant, only by controlling the chemistry and engineering, the interfacial regions at the grain boundaries, the dielectric loss can be suppressed remarkably while retaining the giant dielectric constant.…”
Section: Sintering and Dielectric Propertiesmentioning
confidence: 99%
“…Along with the development of novel complex perovskite oxide materials, a large number of synthetic strategies have recently been developed to produce CTO materials of different sizes and morphologies [8][9][10][11][12][13][14][15]. In this context, it is well known that the polymeric precursor method is a simple, clean, and efficient approach to fabricate complex functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is well known that the polymeric precursor method is a simple, clean, and efficient approach to fabricate complex functional materials. It also offers excellent chemical homogeneity and precise stoichiometric control during heat treatments at relatively low temperatures [9,15,16]. Hence, this synthetic strategy substantially reduces the presence of segregated phases and does not require long annealing periods compared with other synthetic methods [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties of CCTO materials can be influenced by the Ca/Cu ratio [12][13][14][15][16]. Consequently, the dielectric permittivity, resistivity, and density of CCTO materials are closely related to the segregation of CuO at the grain boundaries [12,13].…”
Section: Introductionmentioning
confidence: 99%